Influences of Talking Stick Model Assisted by PowerpointMedia to Primary School Students’ Critical Thinking Skills - Ahadia Irawati, Fenia; Eko Pramono, Suwito; Setiawan, Deni (Educational Management, 2020)
Based on constitution number 20 Year 2003 about educational system concerning with National education, it asserts that teaching - learning activity should be PAIKEM in nature. To promote PAIKEM learning, teachers should design the learning by cooperative learning model. In Public Primary School 2 Sambung, the teacher had implemented 2013 curriculum but the realization was not fully utilized PAIKEM well. This research aims to find out Talking Stick model assisted by PowerPoint medium influences to students’ critical thinking skills. This qualitative descriptive research took population from Public Primary School in Sultan Agung cluster, Kudus municipality. Then, the sample was taken by purposive sampling, resulting to IV A class of Public Primary School 2 Sambung which consisted of 22 students as experimental group. Meanwhile, the control group was obtained from IV B class, consisting of 18 students. Techniques of collecting data were test - essay test, and non-test - documentation and observation. The calculation of independent sample t-test showed that tcount0.4, meaning that tcount>ttabel.Result of experimental group's N-gain score was 0.65, categorized moderate. Meanwhile, the control group obtained 0.35, categorized moderate. It showed there was improvement of critical thinking skill after being intervened by talking stick assisted by PowerPoint media.